Behaviour change techniques associated with adherence to prescribed exercise in patients with persistent musculoskeletal pain: Systematic review - Meade, Laura B.; Bearne, Lindsay M.; Sweeney, Louise H.; Alageel, Samah H.; Godfrey, Emma L. (British journal of health psychology, 2019)
Purpose Exercise (planned, structured, repetitive movement) improves pain and function in people with persistent musculoskeletal pain (PMSK), but adherence is often poor. This systematic review evaluates the evidence from randomized controlled trials (RCTs) on the effectiveness of interventions to improve exercise adherence in people with PMSK and describes the content, context, and theoretical underpinning of behaviour change interventions designed to increase adherence. Methods Nine electronic databases were searched from inception dates to August 2017. Studies were included if they were RCTs that included adults with PMSK ≥3 months; ≥one measure of exercise adherence, exercise prescribed to both groups, and employed ≥one behaviour change technique (BCT) in the treatment group. Independent data extraction, theory coding, BCT taxonomy coding, and quality assessment using Cochrane Risk of Bias (RoB) tool was conducted by two reviewers. Results Eight RCTs (five low, three high RoB) met inclusion criteria. Five trials reported between‐group differences in exercise adherence, favouring the treatment group. Three trials reported theoretical underpinning. There was moderate evidence that five BCTs, social support, goal setting, instruction of behaviour, demonstration of behaviour, and practice/rehearsal, improved exercise adherence. Interventions employing ≤seven BCTs, unique to those included in the control group, were most effective at enhancing exercise adherence. Conclusions Limited moderate‐quality evidence supports using a small number of BCTs to enhance exercise adherence in people with PMSK. Further research should explore the associations and synergies between BCTs and explicitly report how theory was utilized. This may inform recommendations for health care professionals working with this population. Statement of contribution What is already known on this subject? Exercise (i.e., planned, structured, repetitive movements) improves pain and function in people with persistent musculoskeletal pain (PMSK). Many people with PMSK do not adhere to exercises prescribed by a health care professional. Little research has explored how to enhance adherence to prescribed exercise in people with PMSK. What does this study add? Moderate‐quality evidence from eight trials suggests behaviour change interventions enhance exercise adherence. Social support, goal setting, demonstration, instruction, and rehearsal were employed in effective interventions. Interventions with ≤7 behaviour change techniques were more effective at improving adherence than those employing >7.